2017
DOI: 10.1107/s1600577517001850
|View full text |Cite
|
Sign up to set email alerts
|

Uranium XAFS analysis of kidney from rats exposed to uranium

Abstract: The kidney is the critical target of uranium exposure because uranium accumulates in the proximal tubules and causes tubular damage, but the chemical nature of uranium in kidney, such as its chemical status in the toxic target site, is poorly understood. Micro-X-ray absorption fine-structure (mXAFS) analysis was used to examine renal thin sections of rats exposed to uranyl acetate. The U L III -edge X-ray absorption near-edge structure spectra of bulk renal specimens obtained at various toxicological phases we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Our previous XAFS study of uranium showed that the XANES spectrum of uranium absorbed into cellulose phosphate under biological conditions (pH 7.4) was similar to that of UA, uranium (VI) [16], indicating that interactions between uranyl ions (VI) and phosphorus could explain the uranium colocalization in the S3 segments. Most of the uranium that accumulated in the kidneys was uranium (VI), but some had an edge that slightly shifted towards lower energy, meaning that uranium was reduced after administration [16].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous XAFS study of uranium showed that the XANES spectrum of uranium absorbed into cellulose phosphate under biological conditions (pH 7.4) was similar to that of UA, uranium (VI) [16], indicating that interactions between uranyl ions (VI) and phosphorus could explain the uranium colocalization in the S3 segments. Most of the uranium that accumulated in the kidneys was uranium (VI), but some had an edge that slightly shifted towards lower energy, meaning that uranium was reduced after administration [16].…”
Section: Resultsmentioning
confidence: 99%
“…Our previous XAFS study of uranium showed that the XANES spectrum of uranium absorbed into cellulose phosphate under biological conditions (pH 7.4) was similar to that of UA, uranium (VI) [16], indicating that interactions between uranyl ions (VI) and phosphorus could explain the uranium colocalization in the S3 segments. Most of the uranium that accumulated in the kidneys was uranium (VI), but some had an edge that slightly shifted towards lower energy, meaning that uranium was reduced after administration [16]. The reduction of uranium (VI) to (V) or (IV) results in a slight shift of the edge jump at 1–2 eV and a slight narrower peak [17,18], indicating that the proximal tubules without concentrated phosphorus could contain chemical forms of uranium that varied between (VI) and a reduced form.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The precise location and accurate quantification of uranium in rodents' kidneys would facilitate trustworthy information for reconstructing a more realistic dosimetry model for a better estimation of health risk that could be related to renal dysfunction or cancer occurrence in workers exposed to uranium. To date, few quantitative studies have been carried out employing high-energy synchrotron radiation X-ray fluorescence (SR-XRF) analysis and X-ray absorption fine structure (XAFS) [16,17]. Unfortunately, the limited access to these analytical techniques limits considerably its daily use for routine analysis [18].…”
Section: Introductionmentioning
confidence: 99%
“…The uranium-concentrated areas were still detected during recovery [17]. Uranium in these areas was partially reduced [18]. In addition, phosphorus and potassium were colocalized in some of these areas [19].…”
Section: Introductionmentioning
confidence: 94%